UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA PELAJARAN MATEMATIKA DI KELAS VASDN 007 BAGAN BESAR - Murrah, Murrah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Background research is poor learning outcomes in Mathematics. This is confirmed by observations of researchers from 20 students only 4 students who complete study results. This research is a class action, the study aims to improve learning outcomes through the implementation of STAD cooperative method. This study was conducted SDN 007 Bagan Besar. The subjects were students of class V A. The instrument used for data collection is an oral test and a written test conducted after the learning process. The results showed that the application of STAD cooperative method can improve learning outcomes in mathematics. This is clearly evident from the findings that: (1) in the first cycle mastery learning outcomes increased by 40%; (2) in the second cycle ketuntsana learning outcomes increased by 75%. Based on the results and the above discussion, it can be concluded that through the implementation of STAD cooperative learning methods to improve learning outcomes math class student V SDN 007 A Bagan Besar .